Pooling, Savings, and Prevention Mitigating the Risk of Old Age Poverty in Chile - Packard, G. Truman (The World Bank, 2002)
Using data collected in a survey on risk and social insurance in Chile, Packard finds that workers who entered the labor market after the pension reform of 1981 have a greater "contribution density" than those who contributed to the previous social security system. Further, the expectation of care from children and the amount spent on their education significantly lowers the likelihood of contribution to the pension system. Workers who have met the contributory requirements to qualify for the minimum pension guaranteed by the government are significantly less likely to continue making contributions. The likelihood of contributions beyond the eligibility threshold being lowered further, the greater the market rental value of respondents' homes. Furthermore, individuals with a greater tolerance for risk contribute, suggesting that there are retirement security investments in Chile that are perceived as relatively less risky than saving in the reformed pension system. The results indicate that housing could be one such investment. This paper—a product of the Human Development Sector Unit, Latin America and the Caribbean Region—is part of a regional study on social security reform. The author may be contacted at tpackard@worldbank.org